Purification, Characterization and Antifungal Activity of Chitinase from Serratia marcescens Isolated from Fresh Vegetables - Zeki, N. H.; Muslim, S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Seven [35%] and five [25%] Serratia marcescens  isolates were obtained out of 20 samples of lettuce and 20 samples of spinach, respectively, taken from different locations in a farm in Baghdad city. The isolate that produced chitinase in higher level was chosen to purify chitinase through several stages of purification including: ammonium sulfate precipitation, DEAE- sephadex ion exchange chromatograpgy and sephadex G-200 gel filtration with 89.5- fold purification and 30% recovery.       The purified chitinase was characterized and the molecular weight of enzyme was 59000 daltons by using gel filtration chromatography. The optimum pH and temperature of the purified chitinase were 6.0 and 50Â° c, respectively, and the purified enzyme was stable on pH 5-7 up to 50Â° c. The enzyme was activated by Ca+2 , Cu+2 , Mg+2  and inhibited by Hg+2. In addition , Triton x-100 and n-ethylmaleimide increased the chitinase activity while EDTA, methanol, ethanol and acetone inhibited enzyme activity; and this indicates that chitinase  is a metaloenzyme. Chitinase showed stronger inhibitory activity to Fusarium solaini compared with Aspergillus flavus with percent of inhibition 83 and 69%, respectively . Therefore, this research leads to increase interest by using the chitinase as biocontrol agent of phytopathogenic fungi and insects , production of chito â€“oligosaccharides,preparartion of  sphaeroplast and protoplast from yeast and fungi and bioconversion of chitin waste to single cell protein for animal feed.